Manejo del dolor por enfermería relacionado a la satisfacción del paciente postoperado del Hospital Regional de Loreto, Punchana 2024 - Enriquez Ahuanari, Lizeth Dolores (2024)
Every patient undergoing surgery experiences pain, and therefore, the management of postoperative pain is crucial for proper recovery and patient satisfaction. Approximately 90% of patients experience postoperative pain, with around 60% describing it as moderate to severe within the first 24 hours. Pain relief is achieved through both pharmacological and non-pharmacological treatments, and early assessment by nursing professionals, along with the implementation of the appropriate treatment, enhances the effectiveness of pain management. The aim of this study is to determine the relationship between pain management by nursing staff and patient satisfaction after surgery. The specific objectives are: to characterize the study subjects by age, sex, occupation, educational level, and type of surgery; to identify pain management practices by nursing staff; to assess patient satisfaction post surgery; and to establish the relationship between pain management by nursing and patient satisfaction post-surgery at the Hospital Regional de Loreto, Punchana, 2024. The methodology is descriptive, with a non experimental correlational design. The population consists of 275 male and female postoperative patients. Two questionnaires are used as instruments, one for pain management and another for patient satisfaction. Data analysis will be performed using the SPSS statistical package, version 25, with the Chi square test (X2), considering a 95% significance level for α = 0.05. The results provide a framework for understanding the variables involved, which will serve as a foundation for future studies on this topic. It offers a validated and contextualized instrument for healthcare professionals caring for surgical patients to develop strategies for better pain management.